An analytical review of sustainable development of American reading promotion policies - Dong, X; Liu, Yan Quan (Library, 2018)
Keywords: dept.ils; ⛔ No DOI found

Service mode of smart recommendation based on knowledge discovery - Wang, Y; Dong, X; Liu, Yan Quan (Research on Library Science, 2018)
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Service Mode of Smart Recommendation Based on Knowledge Discovery/基于知识挖掘的图书馆智慧推荐服务模式 - Wang, Y.; Dong, X.; Liu, Y. Q. (Research on Library Science/图书馆学研究, 2018)

Investigation of experimental observables in search of the chiral magnetic effect in heavy-ion collisions in the STAR experiment - Choudhury, S.; Dong, X.; Drachenberg, J. L.; Dunlop, J. C.; Esumi, ShinIchi; Feng, Yicheng; Finch, E.; Hu, Yu; Jia, Jiangyong; Lauret, Jerome; Li, Wei; Liao, Jinfeng; et al. (Chinese Physics C, 2022)
The chiral magnetic effect (CME) is a novel transport phenomenon, arising from the interplay between quantum anomalies and strong magnetic fields in chiral systems. In high-energy nuclear collisions, the CME may survive the expansion of the quark-gluon plasma fireball and be detected in experiments. Over the past two decades, experimental searches for the CME have attracted extensive interest at the Relativistic Heavy Ion Collider (RHIC) and the Large Hadron Collider (LHC). The main goal of this study is to investigate three pertinent experimental approaches: the correlator, the R correlator, and the signed balance functions. We exploit simple Monte Carlo simulations and a realistic event generator (EBE-AVFD) to verify the equivalence of the core components among these methods and to ascertain their sensitivities to the CME signal and the background contributions for the isobar collisions at the RHIC. © 2022 Chinese Physical Society and the Institute of High Energy Physics of the Chinese Academy of Sciences and the Institute of Modern Physics of the Chinese Academy of Sciences and IOP Publishing Ltd.
11 citations (Crossref) [2023-10-31] https://iopscience.iop.org/article/10.1088/1674-1137/ac2a1f ; http://hepnp.ihep.ac.cn/article/id/55afc331-6758-45b3-97ce-444828b72c70 ; http://cpc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; http://csnsdoc.ihep.ac.cn/article/doi/10.1088/1674-1137/ac2a1f ; https://inspirehep.net/literature/1863127
Keywords: dept.phy; peer-reviewed

ϒ production in U + U collisions at sNN =193 GeV measured with the STAR experiment ϒ PRODUCTION in U + U COLLISIONS at ⋯ L. ADAMCZYK et al. - Adamczyk, Leszek; Adkins, J. K.; Agakishiev, G.; Aggarwal, M. M.; Ahammed, Zubayer; Alekseev, I. G.; Anderson, Derek; Aoyama, Ryo; Aparin, A.; Arkhipkin, D.; Aschenauer, E. C.; Ashraf, Muhammad Usman; et al. (Physical Review C, 2016)
18 citations (Crossref) [2023-10-31] Citation Key Alias: pop00056 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed